Respuesta :

Answer:

[tex]\sf x=\sqrt{6} +4[/tex]

[tex]\sf x=4-\sqrt{6}[/tex]

Step-by-step explanation:

[tex]\sf x^2-8x+10=0[/tex]

Equations of the form ax^2+bx+c=0 can be solved by the quadratic formula:

[tex]\boxed{\sf \cfrac{-b\pm \sqrt{b^2-4ac}}{2a}}[/tex]

Quadratic formula gives you two solutions one when (±) addition and one when (±) is a subtraction:

[tex]\sf x^2-8x+10=0[/tex]

Substitute:

[tex]a:1[/tex]

[tex]b:-8[/tex]

[tex]c:10[/tex]

[tex]\sf x=\cfrac{-\left(-8\right)\pm \sqrt{\left(-8\right)^2-4\times \:1\cdot \:10}}{2\times \:1}[/tex]

Square -8, and multiply -4 by 10:

[tex]\sf x=\cfrac{(-8)\pm\sqrt{64-40} }{2}[/tex]

Add 64 and - 40, and take the square root of 24:

[tex]\sf x=\cfrac{-(-8)\pm2\sqrt{6} }{2}[/tex]

-(-8)= 8

[tex]\sf x=\cfrac{8\pm2\sqrt{6} }{2}[/tex]

Now solve when (±) is a plus and then solve when it is a minus:-

[tex]\sf x=\sqrt{6} +4[/tex]

[tex]\sf x=4-\sqrt{6}[/tex]

____________________________

ACCESS MORE